2022
DOI: 10.1111/exd.14637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mucopolysaccharide polysulphate on tight junction barrier in human epidermal keratinocytes

Abstract: Tight junctions (TJs) play important roles in epidermal barrier function and their dysfunction is involved in the pathogenesis of various skin diseases, including atopic dermatitis (AD). Mucopolysaccharide polysulphate (MPS) is the active ingredient of a moisturizing agent used to treat xerosis in patients with AD; however, its mechanism of action on TJ barrier function remains unclear. To elucidate the effects of MPS on TJs, adult human epidermal keratinocyte (HEKa) cells were exposed to MPS, subjected to Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…This discrepancy may be because MPS also affects barrier function-related factors, like TJ-related proteins except for claudin-1 and differentiation markers, in keratinocytes. In our previous report [31], MPS increased the protein levels of claudin-1 and ZO-1, a TJ constituent, in normal HEKa. Wen et al [32] reported that topical MPS-containing products increased mRNA expressions of epidermal differentiation markers and lipid synthetic enzymes in clobetasol propionate-containing product-induced skin barrier impairment in mice.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This discrepancy may be because MPS also affects barrier function-related factors, like TJ-related proteins except for claudin-1 and differentiation markers, in keratinocytes. In our previous report [31], MPS increased the protein levels of claudin-1 and ZO-1, a TJ constituent, in normal HEKa. Wen et al [32] reported that topical MPS-containing products increased mRNA expressions of epidermal differentiation markers and lipid synthetic enzymes in clobetasol propionate-containing product-induced skin barrier impairment in mice.…”
Section: Discussionmentioning
confidence: 78%
“…The interaction of hyaluronic acid with its receptor CD44 has also been reported to inhibit CP-induced skin atrophy [29], and in the CD44 knockout keratinocytes, claudin-1 expression is reduced and TJ barrier formation is delayed [37]. Recently, it has been reported that MPS-containing creams suppress CP-induced skin atrophy in mice and show efficacy against CP-induced impairment of the epidermal permeability barrier [32] and that treatment of keratinocytes with MPS increases TJ-related proteins such as claudin-1 and ZO-1 [31]. In consideration of these reports, it is suggested that CD44 activation may be involved in the increased expression of TJ-related proteins in MPS, but the relationship with CD44 signaling needs to be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…FD−4 is a marker of changes in intestinal permeability and the intestinal barrier [ 23 ]. TJ-related proteins, including ZO−1, occludin, and claudin−1, play important roles in maintaining intercellular connections and cell barriers [ 24 , 25 ]. Occludin plays an important role in maintaining the intestinal TEER, has adhesion functions, and serves as a fence.…”
Section: Discussionmentioning
confidence: 99%
“…Claudin−1 affects the permeability of intercellular substances, especially cations, forming a selective paracellular ion channel. ZO−1 binds to a variety of cytoskeletal proteins and plays a supporting role in TJs [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased claudin-1 protein expression is strongly associated with AD severity. Abnormal filaggrin expression is also prominent in patients with AD [ 6 ]. In addition to skin barrier dysfunction, the key role of Th2 cells in AD has been well documented in relation to the immune response.…”
Section: Introductionmentioning
confidence: 99%